The Effect of Project-Based Learning Model on Narrative Writing Skills and Learning Achievement of Indonesian Language Elementary School Students - Muh Khaedar; Syamsul Alam; Akhiruddin Akhiruddin (JED (Jurnal Etika Demokrasi), 2023)
Abstrak. The purpose of this study was to determine the effect of the project-based learning model on narrative writing skills and learning achievement of Indonesian language elementary school students. This type of research is pre-experimental research in the form of a group Pre Test Post Test Design, which is an experiment that in its implementation, only involves one class as an experimental class without a comparison class (control class). The results showed that the narrative writing skills in Indonesian language subjects of students at the pretest stage using test instruments can be concluded that the narrative writing skills in Indonesian language subjects of Class IV students of SD Inpres Sailong, Gowa Regency have not met the criteria for classical learning achievement completeness because students who are complete are only 4% of 75%.75%. Meanwhile, at the post-test stage using test instruments, it can be said that the level of narrative writing skills in Indonesian language subjects of students after applying the project-based learning model is high, so it can be concluded that narrative writing skills in Indonesian language subjects of Class IV students of SD Inpres Sailong Gowa Regency have met the criteria for classical learning achievement completeness because students who are complete are 92% of 75%. 75%.